2020
DOI: 10.1142/s0129065720500288
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Breath Pacing on Task Switching and Working Memory

Abstract: The cortical and subcortical circuit regulating both cognition and cardiac autonomic interactions are already well established. This circuit has mainly been analyzed from cortex to heart. Thus, the heart rate variability (HRV) is usually considered a reflection of cortical activity. In this paper, we investigate whether HRV changes affect cortical activity. Short-term local autonomic changes were induced by three breathing strategies: spontaneous (Control), normal (NB) and slow paced breathing (SB). We measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
8
1
Order By: Relevance
“…This is based on the coupling of heart beat and respiration with the respiratory sinus arrhythmia, where inhalation is linked to faster HR, and exhalation to slower HR (Angelone & Coulter, 1964; Yasuma & Hayano, 2004). Our findings illustrate that the increase in RMSSD, and hence in cardiac vagal activity, can be seen mostly during slow-paced breathing but not necessarily after, as suggested elsewhere (Bonomini et al, 2020; Kromenacker et al, 2018; You et al, 2021).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This is based on the coupling of heart beat and respiration with the respiratory sinus arrhythmia, where inhalation is linked to faster HR, and exhalation to slower HR (Angelone & Coulter, 1964; Yasuma & Hayano, 2004). Our findings illustrate that the increase in RMSSD, and hence in cardiac vagal activity, can be seen mostly during slow-paced breathing but not necessarily after, as suggested elsewhere (Bonomini et al, 2020; Kromenacker et al, 2018; You et al, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…Decision making does not belong to the core executive functions but is considered a higherorder executive function that relies on core executive functions (Diamond, 2013). Overall, accuracy in inhibition (Laborde, Lentes, et al, 2019), working memory (Bonomini et al, 2020;Prinsloo et al, 2011), and decision making (De Couck et al, 2019) was found to be improved, while no influence was found on inhibition in Prinsloo et al (2011). Processing speed remained unchanged (Bonomini et al, 2020;Laborde, Lentes, et al, 2019).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, slow and rhythmic breath-based meditation (e.g., Sudarshan Kriya) has shown significant effects on reducing post-traumatic stress disorder (PTSD) symptoms, hyperarousal, and anxiety in United States military combat veterans ( Seppala et al, 2014 ; Schulz-Heik et al, 2022 ), and breath-based mindfulness has been shown to have a positive influence on participants’ cognitive performance—especially WM performance ( Mrazek et al, 2012 ; Quach et al, 2016 ). Even a simple slow breathing intervention can improve participants’ heart rate variability (HRV) and multitasking test performance ( Bonomini et al, 2020 ). Taken together, this evidence suggests that slow rhythmic breathing has the potential to restore or improve cognitive function.…”
Section: Introductionmentioning
confidence: 99%